Nutraceutical emulsion containing valproic acid (NE-VPA): a drug delivery system for reversion of seizures in zebrafish larvae epilepsy model - Feas, Daniela Agustina (2017)
Valproic acid (VPA) is an antiepileptic drug, which is currently used in neurodegenerative diseases. However, a high dose is required to obtain a therapeutic effect. Long-chain polyunsaturated fatty acids (PUFAs), such as omega 3 and omega 6, are efficient complements in treatments for neurological diseases. Previous studies have reported that a dietary supplement containing PUFAs together with the administration of antiepileptic drugs significantly reduces the frequency of seizures. Based on this, the main goal of this work was to obtain a complex based on VPA encapsulation in an oil/water (o/w) nutraceutical emulsion (NE) enriched with PUFAs for oral administration. Besides, encapsulation of VPA might reduce its dose and increase its therapeutic effect. In order to study its effect, we used a zebrafish larvae model of induced epileptiform behavior with the proconvulsant drug pentylenetetrazol (PTZ). Results have shown that when 100 μM VPA and fatty acids were combined in the NE (NE-VPA), the epileptiform behavior of PTZ-treated zebrafish larvae decreased significantly. Additionally, morphological changes, hepatotoxicity, lethality and heart rate were studied. Despite the fact that a high dose of VPA exerted a cardiotoxic effect, this was no longer detected after addition of this drug in the NE. This treatment exerted a significant antiepileptic effect and did not result in highly toxic or lethal effects. In order to develop an improved pharmaceutical treatment, and considering that all the components used are FDA approved for consumption, the NE-VPA selected might be easily incorporated into clinical trials.